Knowledge of Health Conditions Associated With Sugar-Sweetened Beverage Intake Is Low Among US Hispanic Adults. Issue 1 (January 2019) - Park, Sohyun; Ayala, Guadalupe X.; Sharkey, Joseph R.; Blanck, Heidi M.
Purpose: To examine associations between knowledge of health conditions and sugar-sweetened beverage (SSB) intake among Hispanic adults. Design: Quantitative, cross-sectional study. Setting: The 2015 Estilos survey data. Participants: One thousand US Hispanic adults (≥18 years). Measures: The outcome variable was frequency of SSB intake (regular soda, fruit drink, sports/energy drink, and sweetened coffee/tea drink). Exposure variables were knowledge of 6 SSB-related health conditions (weight gain, diabetes, dental caries, high cholesterol, heart disease, and hypertension). Analysis: Six multinomial logistic regression models were used to estimate adjusted odds ratios for consuming SSBs ≥3 times/day (high intake), in relation to knowledge of SSB-related health conditions. Results: Overall, 58% of Hispanic adults consumed SSBs ≥2 times/day and 36% consumed SSBs ≥3 times/day. Although most identified that weight gain (75%) and diabetes (76%) were related to drinking SSBs, only half identified this relation with dental caries (57%) and hypertension (41%). Even fewer identified high cholesterol (32%) and heart disease (32%) as related. In crude analyses, SSB intake was significantly associated with knowledge of the associations between SSBs and weight gain, dental caries, and heart disease; however, after adjusting for sociodemographics and acculturation, associations were no longer significant. Conclusions: Although SSB intake was very high, knowledge of SSB-related health conditions was low and was not related to high SSB intake among US Hispanic adults. Education efforts alone may not be adequate for Hispanic adults to change their behaviors.